The Transformation of Technical Thinking and the Educational Process of Entrepreneurial Ability During the Formation of a Market Economy - Laužackas, Rimantas; Lydeka, Zigmas (Ekonomika, 1997)
The end of the twentieth century is witnessing many meaningful transformations in the economies of post-socialist countries. The essential point is that these changes in a command economy which were formed by certain methods of thinking and action are being transformed and created in principle in new ways: if in the command economy political-ideological and technical thinking prevailed, accompanied by appropriate activity, then in a market economy, economical thinking and business activity is obvious; likewise, in the previous system, the principal economic participants were political ideogists and technical workers, while in a market economy it is businesspeople. Thus, during the transformation period, a vast number of technical “thought” workers have become “businesspeople”. In Lithuania the appearance of businesspeople is inevitable, albeit uncontrollable, though it could be regulated in some way.This article analyses three methods of economic adaptation for engineers: preservation of loyalty to the previous professional activity; voluntary change of profession without preparation for requalification; early entry into material ability nurturing processes. The above mentioned problem in Lithuania is being solved in two ways. There are radical curriculum reforms taking place in the higher schools of engineering and much attention is being paid to basic general qualifications with professional mobility and the development of flexibility. The other way is a rapid development system of improving qualifications, modern universities the participation of private sector institutions in reimbursing the engineers seeking requalification.